Soluções de certas congruências quadráticas - Fortes, Renato dos Santos Resende (2017)
In this paper we intend to determine the solutions of some quadratic congruences of the form x 2 ≡ a (mod p k ), in which p is a prime and k a natural number and the congruence x 2 ≡ a (mod m), in what respect m is a compound number. We will present the Tonelli-Shanks algorithm to solve congruences x 2 ≡ a (mod p), for p odd cousin. As the application will determine the entire solutions of the equation x 2 − py = a.